Evaluation of Family Clusters of Children with SARS-CoV-2: Children Do Not Play the Leading Role - (:unkn) unknown (GEORG THIEME VERLAG KG, 2022)
Objective The exact role of children in the household transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is not clear. In this study, we investigated the role of children with coronavirus disease 2019 (COVID-19) in household transmission by identifying the index patient and contact tracing the household members. Methods A total of 103 children with COVID-19 who attended Marmara University Pendik Training and Research Hospital, Istanbul, between 25th March and 27th May 2020 were included in the study. A family cluster was defined as a group of >= two confirmed cases of SARS-CoV-2 in the same family, and a household contact (HHC) was defined as any person who had stayed in the same residence. Results In total, 78 family clusters and 307 HHCs belonging to these clusters were screened. In only four clusters was the index case determined to be in the pediatric age group (5.1%). Fathers, mothers, grandparents, and adult siblings were identified as the index cases in 37 (47.4%), 18 (23.0%), 8 (10.2%), and 6 (7.7%) clusters, respectively. Of the 307 HHCs, 88 were in the pediatric age group, and 39 were SARS-CoV-2 RT-PCR positive. Conclusion Our data showed that SARS-CoV-2 is uncommon in children without any history of contact to a RT-PCR test positive patient. The role of children as the index patient in family clusters is 5.1%, and the actual index case is usually an adult individual who has had an outside contact.
Keywords: children; contact tracing; COVID-19; family cluster; severe acute respiratory syndrome coronavirus 2